Todorov and the discourse of violence and inequality in Western thought - عباس بشرى; مراد محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The West’s denial of the principle of equality of civilizations, and its practice of violence against the other, believing in the right of guardianship and the imposition of control, was the motive for the exhumation of western heritage by Tzvetan Todorov (1939 -2017) aimed at developing a new approach to the issues of modern man, equality and equal opportunities among peoples in the contribution of civilization, stressing that the concept of a clash of civilizations is only a model that justifies interference in the affairs of other countries, and that the denial of equality leads to the rationalization of terror in the West in addition to the obsession of power that does not leave the West behind the west. Todorov refuses to justify the guardianship of one civilization over another under any pretext, as well as calling for the spread of a culture of tolerance, dialogue and recognition of the other.